Analysis Of Carbon Dioxide Reforming Of Methane Via Thermodynamic Equilibrium Approach - Tung, Chun Yaw (Penerbit UTM Press, 2005)

(untitled)
Water Formation Through Reverse Water Gas Shift And Several Other Side Reactions In Carbon Dioxide Reforming Of Methane (CORM) Have Became One Of The Major Process Hurdles That Limits Maximum Hydrogen And Syngas (H2-CO Mixture) Yields. Therefore, It Is Vital That The Study On CORM Thermodynamic Equilibrium Takes Into Consideration The Formation Of Water In The CORM Reaction Network. Due To The Complexity Of The Reaction Network, Lagrange’s Undetermined Multiplier Was Employed In The Present Work And Its Applicability Had Been Proven Throughout This Study. The Equilibrium Compositions Improved Drastically From 600-1000K, But The Temperature Effect Becomes Insignificant Above 1000K. Furthermore, CO/H2 Ratio Close To Unity Can Be Achieved At Lower CO2 /CH4 Feed Ratios But Equal CO2 /CH4 Feed Ratios Is Required To Obtain Higher H2 And CO Yields At Temperature 1000K And Above. These Findings Are In Strong Agreement With Laboratory Experimental Results Reported In Literature.